A circular‐polarized and high‐gain microwave correlation imaging antenna based on rotating elements. Issue 12 (4th November 2022) - Li, Liang; Wang, Shi‐Yu; Chen, Jianzhong; Zhang, Chengwei; Tang, Jing; Su, Tao
Abstract: In this article, a circular‐polarized microwave correlation imaging antenna which is based on rotating elements is presented. The proposed reflect array consists of the circular‐polarized patches, the filling substrates, and the grounded metal plates. It is known that the key to microwave correlation imaging is the construction of a two‐dimensional random radiation field in space. Reflect array antennas use element rotation to achieve phase compensation, different compensation phases can be achieved through different rotation angles of elements, the rotation angle of the element is more random, and a more stray pattern for microwave correlation imaging can be obtained. In the reflector array, every single patch is randomized the rotation angle within a certain range, then a 25 × 25 unit random array is obtained by using HFSS‐MATLAB co‐simulation. The effective area of the feed source irradiated on the reflector is certain each time, so the use of different units to compensate for the difference in phase can make the pattern group obtained with high randomness. For verification, a sample with the overall size of 450 mm × 450 mm is designed, fabricated, and measured. When the feed source and the array move relative to each other, the correlation between the directional patterns is mainly concentrated between 0.5 and 0.8. The radiation field is sufficiently random, and the gain of the pattern can be reached 15 dB when the operating frequency is 12.5 GHz, which can effectively obtain high‐quality imaging results.